Pattern of Colorectal Cancer in Karbala Province of Iraq: Data from Developing Country - Mjali, Ahmed; Hamzah, Sabah Kareem; Darwish, Lamya A A; Al-Rubai, Ali Tahseen Ali (Asian Pacific Journal of Environment and Cancer, 2024)
Background: Globally, there are differences in the prevalence of colorectal cancer (CRC) depending on environmental and demographic factors. Objective: Our study’s objective was to analyze the CRC pattern in the Iraqi province of Karbala, comparing and identifying probable variations with another people. Methods: In Iraq, at the Al-Hussein Cancer Center in Karbala, retrospective descriptive research was conducted on 524 patients who diagnosed with CRC from January 2012 to December 2020. Results: The incidence rate of CRC increased from 3.83 per 100,000 in 2012 to 5.69 per 100,000 in 2020. Among our patients, median age was 55 years. The proportion of males was (54.96%) while the proportion of females was (45.04%) with a M:F ratio of (1.22:1). The most affected anatomical site was colon in (64.89%) and adenocarcinoma was the most frequent histopathology in (67.18%). Unfortunately, more than 46% of cases presented as stage III & IV. Conclusion: This statistical analysis of CRC could be a fundamental knowledge source to analyze epidemiological pattern, to assess development in the last few years and to improve treatment plans.